2014
DOI: 10.1016/j.pscychresns.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling possible effects of childhood physical abuse on gray matter changes in violent offenders with psychopathy

Abstract: Violent offenders with psychopathy present a lifelong pattern of callousness and aggression and fail to benefit from rehabilitation programs. This study presents the first, albeit preliminary, evidence suggesting that some of the structural brain anomalies distinguishing violent offenders with psychopathy may result from physical abuse in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…Furthermore, we found a significant interaction between childhood maltreatment and psychopathy severity, such that individuals high in psychopathy who experienced more extensive histories of childhood abuse (and particularly sexual abuse) showed the greatest impairments in reversal learning. Though it is necessary to replicate these findings, the current results are consistent with previous work by Kolla and colleagues (Kolla, Gregory, Attard, Blackwood, & Hodgins, 2014; Kolla et al, 2013), who have documented significant maltreatment by psychopathy interactions. These results highlight the importance of considering maltreatment history when studying psychopathic offenders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we found a significant interaction between childhood maltreatment and psychopathy severity, such that individuals high in psychopathy who experienced more extensive histories of childhood abuse (and particularly sexual abuse) showed the greatest impairments in reversal learning. Though it is necessary to replicate these findings, the current results are consistent with previous work by Kolla and colleagues (Kolla, Gregory, Attard, Blackwood, & Hodgins, 2014; Kolla et al, 2013), who have documented significant maltreatment by psychopathy interactions. These results highlight the importance of considering maltreatment history when studying psychopathic offenders.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Kolla and colleagues (2013) reported a significant interaction between psychopathy and maltreatment in which childhood physical abuse was associated with greater levels of reactive aggression, but only among individuals high in psychopathy. Similarly, there is preliminary evidence suggesting that some of the structural brain abnormalities documented in psychopathic offenders may in fact relate to childhood physical abuse, rather than the presence of psychopathic traits per se (Kolla, Gregory, Attard, Blackwood & Hodgins, 2014). It is unclear, however, if similar psychopathy and maltreatment interactions emerge within the context of reversal learning, or if substance use history differentially affects the cognitive functioning of psychopathic individuals.…”
mentioning
confidence: 99%
“…Decreases in GMV were seen in the temporal regions (17,110). Most prominent areas of decreased GMV were the superior temporal gyrus (39,41), middle temporal gyrus (27,46), superior temporal sulcus (29,45), fusiform gyrus (25,27), and the temporal poles (30,33,39).…”
Section: Temporal Cortexmentioning
confidence: 96%
“…Children with conduct disorders were found to show lower volumes and cortical thickness in the frontal cortex, cingulate, and insula and lower volumes in the amygdala and the hippocampus (Fahim et al, 2011;Fairchild et al, 2011Fairchild et al, , 2012Huebner et al, 2008;Sterzer, Stadler, Poustka, & Kleinschmidt, 2007;Walhovd, Tamnes, Ostby, Due-Tonnessen, & Fjell, 2012). Two recent studies found that incarcerated male adolescents who committed homicide showed lower gray matter volumes in the medial and lateral temporal lobes, including the hippocampus and posterior insula, than non-homicide offenders (Cope et al, 2014;Kolla, Gregory, Attard, Blackwood, & Hodgins, 2014). Taken together with adult findings, smaller frontal and temporal regions and enlarged striatum are likely to contribute to impaired impulse control and emotional regulation, leading to the use of aggressive acts as a means to resolve conflict or obtain desirable outcomes.…”
Section: Introductionmentioning
confidence: 99%